New Geographies of Tourist Consumption: The Case of Montenegro - Sanja Pekovic; Jovana Vukcevic; Tatjana Stanovic; Djurdjica Perovic (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The aim of this paper is to increase the understanding of the opportunities and obstacles for developing entrepreneurial activities in agro-tourism sector in northern Montenegro. Therefore, this paper, thus, aims to set a framework for studying the role of innovations and entrepreneurship in the development of sustainable agro-tourism through identifying and providing suggestions for overcoming main entrepreneurial obstacles.
Keywords: L83; L26; 330; entrepreneurship; rural development; katun activities; agro-tourism; Montenegro